Increased Value Addition of Liberica as Robusta Additive at Pangkalan Bun Shop - Risca Permata; Saprudin Saprudin; Wandha Atmaka Aji; Andli Setiawan (Tropical Plantation Journal, 2023)
The study aims to calculate the income and added value of businesses that process liberica coffee fruit into ground coffee. This survey lasted for one month, from August 2020 to September 2020. The research place is the KBA Coffee Shop owned by Mr. Sutrisno in South Arut District. The method taken in this study is to use primary data and secondary data. Primary data were obtained through live interviews using a series of questions. Secondary data were obtained through supporting literature and their relation to this study.  The data analysis methods used in this study are: (1) calculating the business income of liberica coffee fruit processed into coffee grounds, (2) calculating the added value of liberica coffee grounds. The results of the study showed that the Liberica coffee ground processing business provided income to Mr. Sutrisno of Rp. 2 million. 17,991,111.13 per month. The added value enjoyed by KBA coffee shop owners is Rp. 22,830 / Kg of raw materials used. This added value is what KBA Coffee Shop obtains when using 1 kg of raw materials.